2010
DOI: 10.1007/s10551-010-0530-1
|View full text |Cite
|
Sign up to set email alerts
|

Another Look at the Impact of Personal and Organizational Values Congruency

Abstract: managerial values, organizational values clarity, person–organization fit, personal values, congruency, shared values, values,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
3
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 25 publications
5
85
3
7
Order By: Relevance
“…Employees whose values are well congruent with those of their organization will tend to be more positive about their workplace [49,50]. In particular, it has been found that congruence between employees' CSR values and their organization's CSR values is associated with employees' quality of work life [51].…”
Section: Moderating Role Of Person-csr Fitmentioning
confidence: 99%
“…Employees whose values are well congruent with those of their organization will tend to be more positive about their workplace [49,50]. In particular, it has been found that congruence between employees' CSR values and their organization's CSR values is associated with employees' quality of work life [51].…”
Section: Moderating Role Of Person-csr Fitmentioning
confidence: 99%
“…Wartości mają również istotny wpływ na podejmowanie decyzji w organizacji oraz wybór działań, którym poświęca się czas [Wilson 2003, Jin i Drozdenko 2010, Posner 2010], a zatem wpływają na poziom aktywności (zaangażowanie) pracownika.…”
Section: Wartości Jako Wyznacznik Aktywności Człowiekaunclassified
“…Research shows that where the organization cultivates alignment between organizational and individual values, which is called value congruence in academic literature, it induces more positive employee attitudes such as organizational commitment and job satisfaction (O'Reilly et al, 1991;Silverthorne, 2004;Osftroff et al, 2005;Cennamo and Gardner, 2008;Posner, 2010;Leung and Chaturvedi 2011) Although the values construct is widely evoked in organizational literature, but tends to be compromised by lax conceptualization so that the progress of values research continues to be constrained by the lack of a common theoretical basis (Stackman et al, 2000). It happens, because individuals' values and values of organizations espouse may differ from what they practice (Schein, 1985).…”
Section: Phenomenon Of Personal and Organizational Valuesmentioning
confidence: 99%